Las angosturas de Ancoyacpunku y Muynapunku y ubicación de las tres últimas huakas del primer ceque del Qollasuyu - Carreño-Collatupa, Raúl (2022)
The location of huaka Guamansaui, belonging to the first ceque of Qollasuyu, was until now still unknown. This derives from the fact that it was searched at the site called Angostura (Ancoyacpunku), on the border of San Jerónimo and Saylla districts, province of Cusco. But in the past there was another place called Angostura de Muyna, where the geomorphological setting better fits the chronicle description. There is here a rock-huaka that corresponds to the characterization of Guamansaui made by the chronicler Polo de Ondegardo. This does not alter the assignment of the next two huakas (Guayra and Mayu), since this second Angostura is a windy area also crossed by the Huatanay River. Consequently, the last three huakas of the first ceque of Qollasuyu were located in this second Angostura (Muynapuncu). On the other hand, it is evident that this type of narrow passages or puncus (punkus, pongos) had a special ritual and symbolic meaning in pre-Columbian times.